The Electromagnetic Compatibility Design of Metro Energy-absorption Device Control System - 赵道德; 陈元初; 周立明 (Kongzhi Yu Xinxi Jishu)
This paper introduces the design measures of EMC adopted by the metro energy-absorption device, which is manufactured by Zhuzhou National Engineering Research Center of Converters Co., Ltd. The validity and feasibility are proved by the tests. The test results show that the metro energy absorption device completely reaches EMC standards such as GB/T 24338.6-2009, etc.